2022
DOI: 10.1021/acs.langmuir.2c00554
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Metal–Organic Frameworks as Ultrahigh-Performance Electrocatalysts for the Fuel Cell Cathode: A First-Principles Study

Abstract: Except for metal−organic frameworks (MOFs) with traditional metal− nitrogen sites, MOFs with metal−oxygen sites may also possess good oxygen reduction reaction (ORR) catalytic activity due to their unique electronic structures. Herein, using density functional theory methods, the ORR performances of a series of M 3 (HHTT) 2 (where M is a 3d, 4d, or 5d transition metal and HHTT is 2,3,7,8,12,13hexahydroxytetraazanaphthotetraphene)) catalysts are explored. The binding energy (ΔE species ) results suggest that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…There is a certain scaling relationship between the adsorption of intermediates and the catalytic activity of the catalyst. For the ORR, when Δ E *OH is less than about –2.5 eV, ORR activity becomes better as the adsorption weakens. It can be seen that LaN 4 C 2 –III/IV@Gra exhibits weaker OH adsorption in comparison with others, implying better ORR activity. Also, they exhibit appropriate adsorption strength for O 2 , making the OER reaction products more easily desorbed, thus potentially possessing excellent bifunctional activity.…”
Section: Resultsmentioning
confidence: 96%
“…There is a certain scaling relationship between the adsorption of intermediates and the catalytic activity of the catalyst. For the ORR, when Δ E *OH is less than about –2.5 eV, ORR activity becomes better as the adsorption weakens. It can be seen that LaN 4 C 2 –III/IV@Gra exhibits weaker OH adsorption in comparison with others, implying better ORR activity. Also, they exhibit appropriate adsorption strength for O 2 , making the OER reaction products more easily desorbed, thus potentially possessing excellent bifunctional activity.…”
Section: Resultsmentioning
confidence: 96%
“…18 For NiHHTP, peaks at 4.7, 9.6, and 12.6°r epresent the (100), (200), and (210) planes, respectively, and a peak at 27.8°denotes the (001) plane of the stacked structure: CoNiHHTP shows consistent results (Figure S8a). 45,46 The close matching interplanar distances of PHI and MHHTP's π−π stacking (0.32 and 0.33 nm, respectively) imply that they can be interactively stacked. 18,29,31 The broadened and shifted (002) peak of PHI in NiHHTP/PHI and CoNiHHTP/PHI points toward potential π−π interactions (Figure 1f).…”
Section: Controlled Synthesis and Structure Characterizationmentioning
confidence: 99%
“…Dou et al 22 successfully fabricated 200 μm atomically precise large singlecrystal 2D M 3 (HHTT) 2 (M = Cu and Ni), which exhibits high in-plane conductivity. Chen et al 23 reported that M 3 (HHTT) 2 (M = Fe, Co, Rh, and Ir) exhibits high oxygen reduction reaction activity based on first-principles calculations. Liu et al 24 reported a strong dependence between metal centers and the nitrogen-rich ligands on the electrocatalytic performance.…”
Section: ■ Introductionmentioning
confidence: 99%